2016
DOI: 10.1155/2016/1706812
|View full text |Cite
|
Sign up to set email alerts
|

Graphs Generated by Measures

Abstract: In this paper, a graph is assigned to any probability measure on the -algebra of Borel sets of a topological space. Using this construction, it is proved that given any number (finite or infinite) there exists a nonregular graph such that its clique, chromatic, and dominating number equals .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Researchers try to define a graph illustration for some kind of mathematical aspects. For example see [3] in the lattice literature, [13] in the measure literature and [16] in the real-valued continuous functions literature. The study of translating graph properties to algebraic properties is an interesting subject for mathematicians.…”
Section: Preliminarymentioning
confidence: 99%
“…Researchers try to define a graph illustration for some kind of mathematical aspects. For example see [3] in the lattice literature, [13] in the measure literature and [16] in the real-valued continuous functions literature. The study of translating graph properties to algebraic properties is an interesting subject for mathematicians.…”
Section: Preliminarymentioning
confidence: 99%
“…Beck conjectured that ฯ‡(G) = ฯ‰(G) for the zero divisor graph of R and an arbitrary ring R. But Anderson and Naseer [5] have shown that this is not the case in general, namely they presented an example of a commutative local ring R with 32 elements for which ฯ‡(G) > ฯ‰(G). After that lots of authors have worked on such graphs and found classes of graphs on which Beck's conjecture holds (see for instance [1,2,3,6,7,8,9,14,15,17]).…”
Section: Introductionmentioning
confidence: 99%
“…The researchers tried to define a graph illustration for some kind of mathematical aspects. For example [3] in the lattice literature, [12] in the measure literature, [16] in topology literature and [13] in the linear algebra. The study of translating graph properties to algebraic properties is an interesting subject for mathematicians.…”
Section: Introductionmentioning
confidence: 99%